2016
DOI: 10.1016/j.biocon.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Gendered perceptions of tigers in Chitwan National Park, Nepal

Abstract: The survival of many populations of threatened mammals depends on the willingness of human communities to coexist with them. Gender is an important factor because men and women often have different perceptions of wildlife that influence their willingness to coexist with wildlife. While previous studies have hypothesized what may drive gendered perceptions of wildlife, research investigating the underlying drivers of these differences is lacking, especially in developing countries. The objective of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 69 publications
1
14
1
1
Order By: Relevance
“…While education in general has been known to be positively associated with attitude toward reintroductions (Williams et al, 2002), people with higher education are possibly better equipped to assess the costs and benefits associated with translocation and perceive it as non-beneficial. Also, the attitude of people was found to differ by gender, where women are more supportive of tiger conservation as compared to men, which is contrary to other sites where women are more apprehensive of tiger (Bhattarai and Fischer, 2014;Carter and Allendorf, 2016;Gray et al, 2017).…”
Section: Socio-economic Driverscontrasting
confidence: 62%
“…While education in general has been known to be positively associated with attitude toward reintroductions (Williams et al, 2002), people with higher education are possibly better equipped to assess the costs and benefits associated with translocation and perceive it as non-beneficial. Also, the attitude of people was found to differ by gender, where women are more supportive of tiger conservation as compared to men, which is contrary to other sites where women are more apprehensive of tiger (Bhattarai and Fischer, 2014;Carter and Allendorf, 2016;Gray et al, 2017).…”
Section: Socio-economic Driverscontrasting
confidence: 62%
“…However, recent research has shown that women value benefits, such as conservancy membership, differently to men (Keane et al, 2016) and that women may be less tolerant towards predators than men (e.g. Carter & Allendorf, 2016; Harvey et al, 2017). We would therefore advise that women are included in future surveys relating to attitudes and behavioural intentions towards predators.…”
Section: Discussionmentioning
confidence: 99%
“…However, gender differentiated agricultural roles have been reported broadly, including in South Asia by Agarwal (2000), Upadhyay (2005), and Narayanan and Kumar (2007); in West Asia by Abdelali-Martini et al (2008); in Mexico by Rimarachin Rimarachin Cabrera et al (2001) and Chambers and Chambers and Momsen (2007); and in Africa by Mackenzie (2003) and Howard and Nabanoga (2007). Similarly, Allendorf has documented gender differentiated ecological knowledge with respect to tigers in Nepal (Carter and Allendorf 2016) and a nature reserve in China (Allendorf and Yang 2017) resulting from gender differentiated roles.…”
Section: Changes In Ecological Value (∆M I )mentioning
confidence: 98%